(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
At the end of 1924, the Turkestan ASSR was abolished and replaced by NationalState Institutions. On October 14, 1924, the Kara-Kirghiz Autonomous Region was established. Thanks to this historical event, the dispersed Kyrgyz tribes had the opportunity to unite politically, economically, culturally, and form as a separate nation. At the same time, the literary sphere began to take form and founded a literary circle in Kyrgyzstan. Young people interested in literature created a literary organization and gave it the name “Red Spark”. This was the first step towards professional organization, the creation of a separate literary sphere for newcomer poets.